Performing British Online: Discursive Strategies of Identity and Exclusion in Jubilee’s “5 British People vs 1 Fake” - Tasyani, Fibra Aura; Rofiq, Zainur (Journal Corner of Education, Linguistics, and Literature, 2026)
National identity is increasingly negotiated within digital and mediated spaces, where daily interactions become sites for the reproduction and contestation of belonging. Research on national identity and exclusion is extensive, yet there are notable gaps related to digital social experiments. This study explores the way in which British national identity is discursively constructed and policed in Jubilee’s YouTube experiment “5 British People vs 1 Fake.” By utilizing Wodak’s Discourse-Historical Approach within Critical Discourse Analysis, the study analyzes the aspects of Britishness in the discourse and how Wodak’s discursive strategies of identity construction are used to exclude non-British participants. The study uses a qualitative approach and requires 6 British participants in Jubilee’s experiment with one faking their identity. After selecting the transcribed excerpts, the researcher identifies four discursive strategies such as constructive, perpetuation and justification, transformative, and destructive that operate across micro, meso, and macro levels of discourse. The findings reveal that everyday cultural knowledge, such as familiarity with local geography, food, schooling systems, and football, functions as an essential aspect for legitimate national membership. Through Wodak’s discursive strategies, participants with transnational backgrounds are viewed as suspicious or less authentic, illustrating how hybrid identities challenge dominant notions of Britishness. The discussion situates these findings within debates on everyday nationalism and the politics of belonging, arguing that digital social experiments justify exclusionary practices disguised as entertainment. This research enhances the understanding of national identity by demonstrating how digital media settings enable subtle yet powerful forms of boundary-making and exclusion.